2016
DOI: 10.14419/ijans.v5i2.6312
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among glaucoma patient at upper Egypt

Abstract: Aim: To assess the awareness among glaucoma patients at Upper Egypt Governorate hospitals. Research design: Descriptive cross sectional research design was used in this study Setting: The study was conducted in ophthalmology outpatient clinics (male & female) at Assiut University Hospital & Al-rmad Hospital, Elmina and Sohag Governorate. Subjects: The sample of this study total coverage of glaucoma patients included (1000), the researcher taking the sample during one year, this sample aged 50 years and above. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…10 In another study among glaucoma patients in Upper Egypt, 84.5% of patients were unaware about glaucoma. 11 This indicated the need of work and certain strategies to increase the knowledge of glaucoma and also self-care practice as it has importance for improving patient adherence for medications.…”
Section: Resultsmentioning
confidence: 99%
“…10 In another study among glaucoma patients in Upper Egypt, 84.5% of patients were unaware about glaucoma. 11 This indicated the need of work and certain strategies to increase the knowledge of glaucoma and also self-care practice as it has importance for improving patient adherence for medications.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] In comparison to the populations of the Middle East, awareness among Jordanians (81.6%) was higher than that in Egyptians (15.5%) and Iranians (46.6%). [ 14 15 ] Only 19.2% of Iranians were able to define it correctly, while 34.1% of Jordanians did. [ 14 ] When compared to Saudi Arabians, one study showed a low level of knowledge about glaucoma among Saudi Arabians (14.8%),[ 16 ] whereas another Saudi study found that 66.5% of respondents had a good level of knowledge about glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to sex, the present study revealed that, approximately two third of control group (64.0%) was males while the study group was equal (50% male and 50% female) this agreed with Abdelazeem, (2021) who reported that more than half of control group were males. Moreover Jullia & Kelly, (2019) who reported that two thirds of control group were males and that was harmonized with Mansour et al, (2019) who found that the majority of control group were males. Also El-Mowafi, (2019) who showed that most control subjects were males while about half of study group were female.…”
Section: Discussionmentioning
confidence: 99%